A Survey on Location Privacy Attacks and Prevention Deployed with IoT in Vehicular Networks. (26th April 2022) - Ahmed, Nadeem; Deng, Zhongliang; Memon, Imran; Hassan, Fayaz; Mohammadani, Khalid H.; Iqbal, Rizwan
Abstract : Vehicular ad hoc networks (VANETs) connect two or more vehicles wirelessly to enable data exchange in an Internet of Things (IoT) environment. In VANETs, location privacy is the most crucial piece of information, and its protection is the top priority. However, the location privacy threats have not been adequately addressed in positioning for IoT in VANETs. This paper provides an overview of location privacy attacks and their solutions to address the problems caused by attacks in any IoT environment. Secondly, we have analyzed specific solutions based on anonymity (pseudonym) and cryptographic solutions using a digital signature technique. This enables to improve user privacy and security of location-based services for IoT in VANET. Moreover, we have proposed a faster 5G solution for the VANETs as it rapidly disseminates the data in fast-moving vehicles.